Peran Job Autonomy dalam memediasi Psychological Empowerment dan Performance - Hidayat, Nurkhavid Banu; Askafi, Eka (Universitas Islam Kadiri, 2026)
This study aims to analyze the effect of job autonomy on employee performance, with psychological empowerment as a mediating variable among BUMDes managers in Kunjang District, Kediri Regency. This research employs a quantitative method with a population of 72 BUMDes managers. The data analysis technique used is Structural Equation Modeling (SEM) with Smart PLS. The results indicate that job autonomy does not significantly affect psychological empowerment, suggesting that the level of job autonomy granted does not directly enhance the psychological empowerment of managers. Additionally, job autonomy does not affect employee performance, indicating that workplace freedom alone is insufficient to improve the productivity, responsiveness, and accountability of BUMDes managers. However, the findings confirm that psychological empowerment has a significant impact on employee performance, highlighting that psychological empowerment through the dimensions of Meaning, Competence, Self-Determination, and Impact plays a crucial role in enhancing their performance. Furthermore, psychological empowerment fails to mediate the relationship between job autonomy and employee performance, implying that other factors are more dominant in determining the effectiveness of job autonomy on performance. The implications of this study emphasize the importance of improving governance, policy support, and strengthening the competencies of BUMDes managers to drive more optimal performance.